Elaine Steinbeck at the Noble Reception - Svenskt Pressfoto:::Creator::::::::::::
Elaine Steinbeck sits between the permanent secretary of the Swedish Academy Anders Osterling (her right) and the winner for medicine James Watson (her left) at the Nobel Prize reception and dinner in Stockholm, 1962. Original in safe